Game of snipers [compact disc, unabridged] - Hunter, Stephen, 1946- (Hunter, Stephen, 1946- Bob Lee Swagger novel., 2019)
Obsessively tracking a sniper with skills that match his own, Bob Lee Swagger teams up with the Mossad, the FBI, and local law enforcement to identify the killer's next target.